ANALISIS KELAYAKAN USAHATANI TEBU DENGAN SISTEM TANAM BONGKAR RATOON DAN KEPRASAN - Daniel Simo (BUANA SAINS, 2026)
The sugarcane plantation sector faces significant challenges in achieving cost efficiency and productivity optimization to support national sugar self-sufficiency. This study aims to analyze and compare the economic feasibility of sugarcane farming between the ratoon cane system (keprasan) and the plant cane system (bongkar ratoon) in Jeding Hamlet, Malang Regency, East Java. A quantitative descriptive-comparative method was employed with purposive location determination. The sample consisted of 50 farmers (7 plant cane and 43 ratoon cane) selected through census sampling. Primary data were collected through structured interviews, while secondary data were obtained from relevant government agencies. Feasibility was assessed using production costs, farm income, and the Revenue–Cost Ratio (R/C Ratio). The results show that the ratoon cane system has a lower average total cost (Rp25,642,047/ha) compared to the plant cane system (Rp26,477,429/ha). Although both systems achieved similar average production (48 tonnes/ha), the ratoon system generated higher income per tonne (Rp588,397) than the plant system (Rp534,209). The R/C Ratio values were 2.28 for ratoon and 2.16 for plant cane, indicating both systems are economically viable, with the ratoon system demonstrating superior short-term efficiency. However, the plant cane system remains essential for long-term productivity sustainability, as it can increase productivity by 15–30% with higher rendement. This study recommends intensive nutrient management, particularly timely nitrogen fertilization, in the ratoon system to reduce productivity decline, along with enhanced extension services regarding optimal ratoon cycles and periodic land rejuvenation.